アラタニ メイメイ サレタ ナンキョク チメイ - 国立極地研究所; コクリツキョクチケンキュウショ; National Institute of Polar Research (1982)
P(論文) 1981年11月24日, 南極地域観測統合推進本部の総会において, 南極地名委員会選定の原案が審議され, 以下の38の地名が新たに命名された。 The Antarctic Place-Names Committee of Japan worked out 38 new place names, which were officially approved by the Japanese Antarctic Research Expedition Headquarters, under date of 24th November 1981. departmental bulletin paper